DETERMINANTS OF POLYTECHNIC EDUCATION IN PRE-SCHOOLS - HONZIKOVA, Jarmila (Journal of Technology and Information Education, 2016)
The study deals with polytechnic education and innovation of approaches to technical education in pre-schools. Pre-school education is characterised by certain specificities which are determined by developmental, cognitive, social and emotional needs of children of this age. The fulfilment of these needs is also in focus of polytechnic education at pre-schools. This theoretical study clarifies the terms working aktivity, working education and polytechnic education, and specifies the objectives of these educational fields. It also shows how to approach the achievement of these objectives in a new and creative way.
Keywords: pre-school; polytechnic education